The disincentive effect of stars : evidence from analyst coverage - Luo, Jiang (2020)
We hypothesize that when the winning odds are eclipsed by the presence of superstars, tournament participants will choose to bow out of the competition. We use the setting of financial analysts to test this hypothesis. We document that nonstar analysts avoid direct competition with star analysts through their coverage decisions. Moreover, nonstars’ reluctance to compete with stars is more pronounced when star analysts are more highly ranked, when winning the tournament carries higher rewards, when institutional ownership is lower, when the firm faces lower uncertainties, and when nonstars are of average ability. In addition, we show that nonstars who avoid direct competitions with stars are more likely to become an Institutional Investor All-star in the future, suggesting that competition avoidance benefits nonstars. Collectively, our results suggest that the presence of superstars discourages others from participating in the tournament.